“Se solo avesse saputo...”: la paura della morte - Sisto, Davide (Filosofia, 2016)
This essay intends to explicate the relationship between the fear of death and the awareness of one’s mortality through a reference to two contemporary cinematographic narrations. Firstly, the focus will be on the reasons for human fear of death and on the consequences of such fear, above all the equivalence between survival and power. Secondly, the essay will try to demonstrate the equivalence between learning to die and unlearning how to serve; the acquired awareness of the tight bond between life and death is an essential starting point to earn one’s independence and freedom within the current socio-political context.